Evaluating Power Reliability Dedicated for Sudden Disruptions: Its Application to Determine Capacity on the Basis of Energy Security - Kosai, Shoki; Tan, Chia Kwang; Yamasue, Eiji (MDPI, 2018)
Given that a continuous power supply is fundamental to the economy and human well-being, development of a self-sustained electrical systemthat can withstand sudden disturbances by employing both renewable energy and storage technology is of significant importance. Most of the existing reliability approaches hardly represent a particular method of analyzing system adapting ability to remain self-sufficient in the short-term after the occurrence of sudden disruptions. In addition, existing reliability indexes are developed based on past experience, hardly covering the prediction of disruption risks. As such, a new electricity reliability quantification approach dedicated for sudden disruptions was established and the newly proposed electricity reliability prediction index was evaluated. The developed index was applied to determine optimal capacity sizing in the context of energy security. The availability of such electricity reliability predictions will allow the facility engineer to make wiser decisions to maintain a continuous power supply even after the occurrence of sudden disturbances. The developed algorithm can be readily implemented in any electrical system network including microgrid and rural electrification.